How Job Insecurity Affects Political Attitudes: Identity Threat Plays a Role. Issue 3 (12th July 2020) - Selenko, Eva; De Witte, Hans
Abstract : This study tests the assumption that job insecurity threatens people's work‐related identities and thereby affects their political attitudes. Work‐related identity threat in times of job insecurity is proposed to happen in two ways: people will fear to lose an important part of their identity (their identity as employed people), and they can also be afraid to gain a negative identity (their feared future self of becoming unemployed). Both identity threats are proposed to lead to more antiegalitarian attitudes and more political leaning to the right. A four‐wave study among 969 employed British employees delivers support for some of the assumptions. In line with the expectations, results of time‐stable structural equation modeling show that job insecurity indeed threatens the identity as an employed person, which leads to an increase in antiegalitarian attitudes over time. Different than expected, identity threat in the form of a heightened identification with the unemployed was not found. Also, people who identified more as unemployed people actually reported fewer antiegalitarian attitudes and shifted their political standing more to the left.